Effect of Four Surface Treatment Methods on the Shear Bond Strength of Resin Cement to Zirconia Ceramics- A Comparative in Vitro Study - Varsha Murthy; Manoharan; Balaji; David Livingstone (Journal of Clinical and Diagnostic Research, 2014)
Background: Improving the retention of zirconia-based ceramics is desirable in order to avoid the failure of crowns and fixed partial dentures .This can be achieved by creating micromechanical retention using surface treatments. Therefore, it becomes necessary to constantly compare and re-evaluate the influence of different surface treatment methods on the bond strength . Aim: To evaluate the effect of four different surface treatments on shear bond strength between zirconia surface and resin cements. Settings and Design: Observational study. Materials and Methods: Twenty five zirconia plate samples were prepared based on ISO standards and were divided into five groups and each group was subjected to following five different surface treatments : no treatment, sandblasting with 110 μm alumina, sandblasting with 250 μm alumina, acid etching with 9.6% hydrofluoric acid and laser radiation on the surface. All the samples were surface disinfected and were embedded in blocks of autopolymerising resin to check shear bond strength on the universal testing machine. Statistical analysis used-data was analyzed using one-way ANOVA and a Post Hoc Bonferroni test. Results: Analysis of the data showed that the highest shear bond strength values were obtained with laser treatment (18.120 ± 0.8159 Mpa). The lowest values were obtained with control group (9.166 ± 0.569 Mpa). Laser treatment increased the shear bond strength values significantly (p<0.05). Conclusion: Surface treatments increased the bond strength between zirconia and resin cement and carbon dioxide laser could be an effective surface treatment for increasing bond strength.